Comparative neonatal outcomes in singleton births from blastocyst transfers or cleavage-stage embryo transfers: a systematic review and meta-analysis - Xingling Wang; Mingze Du; Yichun Guan; Bijun Wang; Junwei Zhang; Zihua Liu (BMC, 2017)
Abstract Background Comparative neonatal outcomes with respect to singleton births from blastocyst transfers or cleavage-state embryo transfers are controversial with respect to which method is superior. Many studies have yielded contradictory results. We performed a systematic review and meta-analysis for the purpose of comparing neonatal outcomes in single births following IVF/ICSI. Methods We searched the Medline, Embase and Cochrane Central Register of Clinical Trials (CCTR) databases until October 2016. Studies and trials that contained neonatal outcomes for singleton births were included. Data were extracted in 2 × 2 tables. The analysis was performed using Rev Man 5.1 software. Risk ratios (RRs) and risk differences, with 95% confidence intervals, were calculated to assess the results of each outcome. Subgroups were applied in all outcomes. Newcastle-Ottawa scale (NOS) checklists were used to assess the quality of the referenced studies. Results Twelve studies met the criteria in this meta-analysis. There was a high risk of preterm birth after blastocyst embryo transfer versus the risk after cleavage-stage transfer (RR: 1.11, 95% CI: 1.01-1.22). For the "only fresh" subgroup, the outcome was coincident (RR: 1.16, 95% CI: 1.06-1.27). For the "fresh and frozen" and "only frozen" subgroups, there were no differences. Patients who received fresh blastocyst embryo transfers had a high risk of very preterm births (RR: 1.16, 95% CI: 1.02-1.31). Finally, cleavage-stage embryo transfers were associated with a high risk of infants who were small for gestational age (0.83, 95% CI: 0.76-0.92) and a low risk of those who were large for gestation age (1.14, 95% CI: 1.04-1.25). Conclusions The risks of preterm and very preterm births increased after fresh blastocyst transfers versus the risks after fresh cleavage-stage embryo transfers. However, in frozen embryo transfers, there were no differences. Blastocyst embryo transfers resulted in high risks of infants who were large for gestational age, and cleavage-stage embryo transfers resulted in high risks of infants who were small for gestational age.